First and Third Isomorphism Theorems for the Dual B-Algebra (European Journal of Pure and Applied Mathematics, 2023)
In this paper, some properties of the dual B-homomorphism are provided, along with the natural dual B-homomorphism and the fundamental theorem of dual B-homomorphisms for dual B-algebras. The first and third isomorphism theorems for the dual B algebra are also presented in the paper.
Keywords: dual B-algebra; quotient dual B-algebra; fundamental theorem of dual B-homomorphism; dual B-isomorphism